Ephemeral territories : representing nation, home, and identity in Canada - Manning, Erin. (Minneapolis : University of Minnesota Press, 2003)
Ephemeral Territories weaves together narratives and representations of Canadian identity--from political philosophy and cultural theory to art and films--to develop and complicate familiar views of identity and selfhood. In a critical engagement with notions of territory, identity, racial difference, separatism, multiculturalism, and homelessness, Manning delves into the question of what it means to be at home in Canada.
Preface: Unmoored; Acknowledgments; Introduction. Close to Home: Canadian Identity, Nationalism, and Errant Politics; 1. An Excess of Seeing: Territorial Imperatives in Canadian Landscape Art; 2. Beyond Accommodation: National Space and Recalcitrant Bodies; 3. Where the Zulu Meets the Mohawk; 4. Face-to-Face with the Incommensurable: Srinivas Krishna's Lulu; 5. Dwelling within the Language of the Other; Conclusion: Water from the Rock; Notes; Bibliography; Index.
Includes bibliographical references (pages 169-181) and index.
Print version record.
JSTOR
Keywords: National characteristics, Canadian; Nationalism -- Canada; Political culture -- Canada; Discourse analysis -- Canada; Human territoriality -- Canada; Home -- Social aspects -- Canada; Regionalism -- Canada; Canada -- Politics and government -- 1980-; Canada -- Intellectual life; Canada -- Ethnic relations; Canadiens; Nationalisme -- Canada; Territorialité humaine -- Canada; Foyer -- Aspect social -- Canada; Régionalisme -- Canada; HISTORY -- Canada -- General; Discourse analysis; Ethnic relations; Human territoriality; Intellectual life; National characteristics, Canadian; Nationalism; Political culture; Politics and government; Regionalism; Canada; Since 1980